From control to causation: Validating a 'complex systems model' of running-related injury development and prevention. (November 2017) - Hulme, A.; Salmon, P.M.; Nielsen, R.O.; Read, G.J.M.; Finch, C.F.
Abstract: Introduction: There is a need for an ecological and complex systems approach for better understanding the development and prevention of running-related injury (RRI). In a previous article, we proposed a prototype model of the Australian recreational distance running system which was based on the Systems Theoretic Accident Mapping and Processes (STAMP) method. That model included the influence of political, organisational, managerial, and sociocultural determinants alongside individual-level factors in relation to RRI development. The purpose of this study was to validate that prototype model by drawing on the expertise of both systems thinking and distance running experts. Materials and methods: This study used a modified Delphi technique involving a series of online surveys (December 2016- March 2017). The initial survey was divided into four sections containing a total of seven questions pertaining to different features associated with the prototype model. Consensus in opinion about the validity of the prototype model was reached when the number of experts who agreed or disagreed with survey statement was ≥75% of the total number of respondents. Results: A total of two Delphi rounds was needed to validate the prototype model. Out of a total of 51 experts who were initially contacted, 50.9% (n = 26) completed the first round of the Delphi, and 92.3% (n = 24) of those in the first round participated in the second. Most of the 24 full participants considered themselves to be a running expert (66.7%), and approximately a third indicated their expertise as a systems thinker (33.3%). After the second round, 91.7% of the experts agreed that the prototype model was a valid description of the Australian distance running system. Conclusion: This is the first study to formally examine the development and prevention of RRI from an ecological and complex systems perspective. The validated model of the Australian distance running system facilitates theoretical advancement in terms of identifying practical system-wide opportunities for the implementation of sustainable RRI prevention interventions. This 'big picture' perspective represents the first step required when thinking about the range of contributory causal factors that affect other system elements, as well as runners' behaviours in relation to RRI risk. Highlights: Distance running is popular form of exercise that promotes numerous physical and psychological health-related benefits. One of the main barriers preventing continued adherence to a running program is musculoskeletal running-related injury (RRI). Alongside traditional scientific applications, a systems thinking perspective can facilitate an enhanced understanding about RRI development and prevention. This study draws on the feedback from a range of subject matter experts to validate an existing prototype systems ergonomics model of the Australian distance running system. The validated model shows that multiple people and organisations 'control' and influence runners' behaviours in relation to RRI risk. This study demonstrates that 'faulty' biomechanics and maladaptive running practices are not wholly responsible for the aetiology of RRI. Future research should continue to utilise a complex systems approach in this space.